Method for treating sub dimension of garden greening waste - SHI ZHENGHUA; DAI KEYAN; LI YIWEI (2018)
The invention relates to a method for treating a sub dimension of garden greening waste, and belongs to the technical field of soil improvement. The method is characterized in that to-be-treated garden greening waste is screened after being pre-treated and fermented once; a primary fermentation product with a relatively small grain size is further digested and decomposed through earthworms, so that a culture medium is finally obtained for being directly turned to the field for improving soil; and the primary fermentation product with a relatively great grain size is subjected to secondary fermentation for a second time, and is dyed, and processed to obtain colorful garden organic covering. The colorful garden organic covering obtained by the method has the attractive effect while improvingsoil quality, and improves wind and rain scouring resistance. 本发明涉及种对园林绿化废弃物分尺寸处理的方法，属于土壤改良技术领域。其将待处理的园林绿化废弃物通过预处理、次发酵之后进行筛分，将粒径较小的次发酵产物通过蚯蚓进步消化分解，最终得到栽培基质，用于直接还田改善土壤；将粒径较大的次发酵产物再继续进行二次发酵，然后进行染色加工处理后得到彩色园林有机覆盖物。本发明处理后可得到彩色园林